2007
DOI: 10.1002/chin.200739209
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Molecular Recognition Pathways within a Family of Gelators with Different Hydrogen Bonding Motifs.

Abstract: General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. AbstractWe report the synthesis of a family of gelators in which alkyl chains are connected to the amino groups of L-lysine methyl ester using a range of different hydrogen bonding linking groups (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A parameterized approach was used to investigate the ability of non-aqueous solvents to dissolve urea. Solvent–solute interactions play an important role in supramolecular chemistry which has led to quantitative studies of the role of solvents in self-assembly processes [ 19 , 20 , 21 , 22 , 23 , 24 ]. The bulk properties (e.g., boiling point, density) or molecular level properties (such as specific intermolecular forces) can be quantified and parameterized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A parameterized approach was used to investigate the ability of non-aqueous solvents to dissolve urea. Solvent–solute interactions play an important role in supramolecular chemistry which has led to quantitative studies of the role of solvents in self-assembly processes [ 19 , 20 , 21 , 22 , 23 , 24 ]. The bulk properties (e.g., boiling point, density) or molecular level properties (such as specific intermolecular forces) can be quantified and parameterized.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters δ P and δ H are described in terms of a combined polar solubility parameter, δ a , and the Kamlet-Taft parameters, π* (a generalized polarity parameter), α (the ability to donate hydrogen bonds), and β (the ability to accept hydrogen bonds). The effects of solvents on the hierarchical assembly of supramolecular polymers in non-aqueous solvents have been studied for self-assembling peptides, and while there was a general correlation between the ability of supramolecular polymers to form and the polar solubility parameter, δ a [ 19 , 20 , 21 , 22 , 23 , 24 ], the precise hydrogen-bonding nature of the solvent in terms of Kamlet-Taft parameters ( i.e. , deconvolution of the hydrogen bond donors and acceptors) was important to fully understand the solvent effects [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…This implies that the gel fibers are solvated and swollen by solvent, lowering the effective concentration of DLT and hence increasing the spin− spin distance as observed using EPR. Inspection of the SEM images of the DLD gel 29 (Figure S5) shows a network of intertwined narrow fibrils which presumably are swollen by solvent in wet gels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the recent literature, the physical gelation of liquids by low-molecular-weight gelators (LMWGs) has been studied with a great deal of interest owing to their impacts in various fields including molecular self-assembly (SA), smart materials, and controlled drug release. Over the last three decades, many LMWGs with excellent gelation abilities have been reported. These include steroids, amide- and urea-type compounds, sugar amphiphiles, and so forth. Most of these gelators, however, were discovered by accident.…”
Section: Introductionmentioning
confidence: 99%
“…The LMWGs reported in the literature fall into two major classes, hydrogen-bond- and non-hydrogen-bond-type gelators. The H-bonding interaction is responsible for the gelation of organic liquids by amide compounds such as amino acids and urea and by hydroxyl compounds such as sugars. However, anthracene, cholesterol, and tropone derivatives are non-hydrogen-bond-based gelators. In fact, in most cases of organogelation, it was observed that H-bonding is the dominant factor.…”
Section: Introductionmentioning
confidence: 99%